A AGENDA 21 COMO HETEROTOPIA DOS AGENTES DOMINANTES NA PRODUÇÃO DE CIDADES NA REGIÃO METROPOLITANA DA GRANDE VITÓRIA-ES - Fernandes, Erick Alessandro Schunig (2022)
This study analyzes Agenda 21 as a model of city organization that, proposed by the State, plays a role in facilitating the interests of dominant agents in the municipalities of Vitória, Vila Velha, Serra, Cariacica and Viana, located in the Metropolitan Region of Grande Vitória (RMGV), Espírito Santo. We assume that Agenda 21 is a document produced by a branch of the state's strategic planning that expresses the interests of those who led its preparation. In this work, we identified Agenda 21 as a heterotopia (FOUCAULT, 2013), whose action proved to be ineffective in proposing a fairer city, as recommended by the guidelines of the global and Brazilian Agenda 21. We believe that this planning model enunciates a discourse, whose exposure is made from a codification, which, in turn, establishes a connection with the myth, by presenting a worldview that attracts people's adhesion. Therefore, we ask why, despite the elaboration of this document in the studied cities, proposing a city accessible to all, it is possible to observe an aggravation of problems in the cities studied, at the same time that there was an increase in the performance of economic agents in these places. We work with the hypothesis that this expansion in the studied municipalities is linked to the construction of a discourse that operates through symbolic mechanisms, aiming to create an idealized city that is present in Agenda 21, but that differs from the real city, obliterating the inequalities and consolidating the hegemonic project of some agents. At the conclusion level, we identified within the Agenda 21 narrative which are the codes used for this purpose, how the image of the cities studied was produced, which are the most prominent areas and who are the agents that led this process and presented a constructed reality at the symbolic level, in order to capture the population's adhesion and legitimize their interests.